Lithium toxicity with prolonged neurologic sequelae following sleeve gastrectomy: A case report and review of literature. Issue 28 (10th July 2020) - Lin, Yi-Hsin; Liu, Sheng-Wen; Wu, Hsein-Lin; Kang, Jung-Cheng; Huang, Kuo-Yang; Huang, Hsuan
Abstract: Rationale: Lithium is the first-line medication for bipolar disorder, given a narrow therapeutic window of 0.8 to 1.2 mEq/L. Change of lithium pharmacokinetics following bariatric surgery may lead to lithium toxicity, which is particularly concerned. Patient concerns: We presented a 39-year-old man with morbid obesity and bipolar affective disorder for 20 years, who was treated with lithium. He developed serious lithium toxicity following sleeve gastrectomy and prolonged neurologic sequelae. Diagnoses: He suffered from persistent watery diarrhea, general weakness, and then drowsy consciousness. Lithium level was checked immediately to be 3.42 mEq/L and lithium toxicity was diagnosed. Interventions: After 3 courses of hemodialysis, his serum lithium level subsequently declined to 0.63 mEq/L, while his consciousness returned normal. Lithium was replaced by lamotrigine. Outcomes: The patient was discharged thirty-five days after admission, while his serum lithium declined to 0.06 mEq/L. Neurologic sequelae were noted by muscle weakness and pain sensation in both feet. The nerve conduction test revealed sensorimotor polyneuropathy with conduction block. He was advised to keep a passive range of motion exercise. Lessons: Although the consensus guideline remains lacking, our report reviewed cases of relevance in the literature and highlighted the awareness of the potential risk of lithium toxicity following bariatric surgery. We suggest close monitoring of the lithium levels and perhaps a dosage adjustment for the postoperative period.